Urgensi Indonesia Meratifikasi The Convention Relating To The Status Of The Refugees 1967 Dan Protocol New York 1967 Mengenai Pengungsi Internasional - Agastya Fatchur Royyan; Sri Lestari Rahayu; Ayub Torry Satriyo Kusumo (BELLI AC PACIS, 2018)
This legal research examines the urgency of Indonesia to ratify the 1951 Convention Relating to the Status of the Refugees and the 1967 New York Protocol on international refugees. Because in Indonesia there is no regulation that can be submitted reference or reference to be able to handle the refugee problem properly and optimally. Given Indonesia’s strategic geographic location for refugees, Indonesia has not ratified the 1951 Protocol to the Status of the Refugees and the 1967 New York Protocol on international refugees, which are modern international refugee law instruments. Both Conventions are also a form of global human rights concern for international refugees. The research used is descriptive normative research through approach of legislation (statue approach). Techniques of collecting legal materials used are literature studies related through print media or internet media. The technique of legal material analysis uses a method of deduction which departs from a general proportion whose truth has been recognized and ends at a more specific conclusion. Based on research and discussion, it can be seen that Indonesia needs a legal instrument that can be used as a reference in overcoming the problem of international refugees optimally. The legal instrument in question is the 1951 Protocol to the Status of the Refugees and the 1967 New York Protocol on international refugees. By ratifying the two instruments of international law, Indonesia will have a legal instrument that can be used as a reference in optimizing the international refugee problem and play a role in international human rights concerns, especially for international refugees.